Direct repair of iatrogenic thoracic duct injury through lymphovenous anastomosis (LVA): A case report. Issue 2 (11th December 2019) - Rodi, Timo; Tung Nguyen, Ba; Fritsche, Elmar; Rajan, Gunesh; Scaglioni, Mario F.
Abstract: This is a case report of a 64‐year‐old male with cancer with an unknown primary and bilateral cervical lymph node metastases. Twelve months after chemo‐, radio‐, immunotherapy, and radical neck dissection, he presented with recurrent cervical metastases. The patient underwent radical revision neck dissection including the deep neck muscles of the cervical plexus and reconstruction with a free anterolateral thigh flap. During tumor resection, parts of the thoracic duct were removed which resulted in a large lymph leak. This was addressed by creating a lymphovenous anastomosis to a branch of the subclavian vein. The flow of lymph was reinstated, and no leak has been observed up to a recent 6‐month follow‐up.